2009
DOI: 10.1525/mp.2009.26.5.401
|View full text |Cite
|
Sign up to set email alerts
|

Fractal Tempo Fluctuation and Pulse Prediction

Abstract: WE INVESTIGATED PEOPLES’ ABILITY TO ADAPT TO THE fluctuating tempi of music performance. In Experiment 1, four pieces from different musical styles were chosen, and performances were recorded from a skilled pianist who was instructed to play with natural expression. Spectral and rescaled range analyses on interbeat interval time-series revealed long-range (1/f type) serial correlations and fractal scaling in each piece. Stimuli for Experiment 2 included two of the performances from Experiment 1, with mechanica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(75 citation statements)
references
References 47 publications
1
71
0
3
Order By: Relevance
“…Listeners significantly prefer music mirroring long-range correlated temporal deviations over uncorrelated (white noise) fluctuations (5,6). LRC are also inherent in the reproduction of both spatial and temporal intervals of single subjects (4,(7)(8)(9) and in musical compositions, such as pitch fluctuations (a simple example of pitch fluctuations is a melody) (10,11) and note lengths (12). The observation of power law correlations in fluctuations of pitch and note length in compositions reflects a hierarchical, selfsimilar structure in these compositions.…”
mentioning
confidence: 99%
“…Listeners significantly prefer music mirroring long-range correlated temporal deviations over uncorrelated (white noise) fluctuations (5,6). LRC are also inherent in the reproduction of both spatial and temporal intervals of single subjects (4,(7)(8)(9) and in musical compositions, such as pitch fluctuations (a simple example of pitch fluctuations is a melody) (10,11) and note lengths (12). The observation of power law correlations in fluctuations of pitch and note length in compositions reflects a hierarchical, selfsimilar structure in these compositions.…”
mentioning
confidence: 99%
“…R ranges from 0 (no stability or no entrainment) to 1 (perfect stability or perfect entrainment), and it has previously been used in quantifying individual timing stability and especially synchronicity and entrainment in dyadic and group timing (Himberg, 2006(Himberg, , 2014Rankin et al, 2009;Lucas et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that humans can successfully identify metre and follow the tempo based off such an expressive rhythm (Epstein, 1995). Rankin et al (2009) conducted a recent study on human beat induction and found that subjects were able to adapt to relatively large fluctuations in tempo resulting from performances of piano music in various genres. The participants could successfully find a pulse at the crotchet (quarter note) or quaver (8 note) metrical level.…”
Section: Expressive Rhythmmentioning
confidence: 99%